An in‐depth neurobehavioral characterization shows anxiety‐like traits, impaired habituation behavior, and restlessness in male Cryptochrome‐deficient mice. (18th May 2020) - Hühne, Anisja; Volkmann, Paul; Stephan, Marius; Rossner, Moritz; Landgraf, Dominic
Abstract: Many psychiatric disorders, for example, anxiety, are accompanied by disturbances of circadian rhythms, including disturbed sleep/wake cycles, changes in locomotor activity, and abnormal endocrine function. Conversely, alternations of circadian rhythms are a risk factor for the development of psychiatric disorders. This assumption is supported by animals with clock gene mutations which often display behaviors that resemble human psychiatric disorders. In this study, we performed an in‐depth behavioral analysis with male mice lacking the central clock genes Cryptochrome 1 and 2 ( Cry1/2 −/− ), which are thus unable to express endogenous circadian rhythms. With wild‐type and Cry1/2 −/− mice, we performed an extensive behavioral analysis to study their cognitive abilities, social behavior, and their expression of depression‐like and anxiety‐like behavior. While Cry1/2 −/− mice showed only mild abnormalities at cognitive and social behavioral levels, they were consistently more anxious than wildtype mice. Anxiety‐like behavior was particularly evident in reduced mobility in new environments, altered ability to habituate, compensatory behavior, and consistent restless behavior across many behavioral tests. In line with their anxiety‐like behavioral phenotype, Cry1/2 −/− mice have higher c‐Fos activity in the amygdala after exposure to an anxiogenic stressor than wild‐type mice. In our study, we identified Cry1/2 −/− mice as animals that qualify as a translational mouse model for anxiety disorder in humans because of its consistent behavior of restlessness, increased immobility, and dysfunctional habituation in new environments. Abstract : Cryptochrome ‐deficient mice with no ability to express endogenous circadian rhythms display pronounced anxiety‐like traits, such as increased restlessness – more switches between mobile (yellow) and immobile (blue) episodes – and increased c‐Fos expression in the amygdala in response to potential threat.